Relationship between the urinary Na/K ratio, diet and hypertension among community-dwelling older adults - Yamanaka, Noriko; Itabashi, Mitsuyo; Fujiwara, Yoshinori; Nofuji, Yu; Abe, Takumi; Kitamura, Akihiko; Shinkai, Shoji; Takebayashi, Toru; Takei, Takashi (Hypertension research, 2023)
The association between the urinary sodium (Na)/potassium (K) ratio and hypertension is well recognized. We investigated whether the urinary Na/K ratio might be associated with hypertension in community-dwelling older adults and whether the association was influenced by habitual dietary patterns. We enrolled a total of 684 older adults (mean age, 76.8 years) and conducted health examinations at Kusatsu, Japan, in 2021. The urinary Na/K ratio was found to be independently associated with systolic blood pressure (SBP) (p < 0.0001), years of education (p = 0.0027), number of cohabitants (p = 0.0175), estimated glomerular filtrate rate (eGFR) (p = 0.0244), and Geriatric Depression Scale short-version (GDS15) score (p = 0.0366). In addition, an unsupervised hierarchical clustering analysis revealed a spectrum of habitual dietary patterns for higher and lower values of the urinary Na/K ratio. The decision tree indicated that the urinary Na/K ratio was associated with the history of milk consumption. A positive history of daily milk consumption predicted a mean urinary Na/K ratio of 2.8, and a negative history of daily milk consumption predicted a mean urinary Na/K ratio of 3.3. Furthermore, the frequency of fruit and vegetable consumption also predicted the urinary Na/K ratio. The relationship between the urinary Na/K ratio and hypertension was influenced by the frequency of consumption of milk, fruits, and vegetables in the subjects. This finding might be due to the influence of education and/or depression. The results suggested the importance of nutritional education in the development of hypertension.